The Strategies of Maxim Flouting In Lincoln Movie Script - Ariwangsa Rahmastra, I Gede Bagus; Gede Sosiowati, I Gusti Ayu (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p15, 2018)
This undergraduate thesis entitled The Strategies of Maxim Flouting in Lincoln Movie Script. It was aimed to analyze maxim flouting in movie script. In more specific terms, it was aimed to identify the strategies applied and the reasons of maxim flouting by the characters in Lincoln movie script. Documentation method and note taking technique were used to collect the data. Qualitative method and descriptive technique , theory of cooperative principle by Grice (1975), and theory of rhetorical strategy by Grundy (2000) were used to analyze the data. Informal method and argumentative technique w ere used to descriptively present the data. All four types of maxim flouting were performed in the movie script. Among six strategies of maxim flouting, four strategies were applied in Lincoln movie script. They are: overstatement, metaphor, rhetorical question, and irony. Various reasons have lead the character to flouting the maxim, they are: demanding, offering, accusing, reprimanding, cursing, threatening, announcing, instructing, greeting, reporting, asserting, and insulting.